Language politeness in the context of Jambi Malay based on gender - Pratiwi, Anggia; Yusrizal; Sri Utaminingsih (Indonesian Research Journal in Education |IRJE|, 2025)
This research aimed to analyze and describe politeness in the learning process between lecturers and PSPBSI STKIP YPM Bangko students in the Jambi Malay context. This research uses a qualitative method with a case study sapproach. The data sources in this research were lecturers and class B students, semester VII, who acted as respondents. The results of the research indicate that (1) politeness in the learning process of lecturers and students is characterized by (a) direct speech acts of declarative, interrogative, and imperative, (b) first-person singular pronoun "I" and second-person singular pronoun "you", (c) greetings, (d) bilingualism (Indonesian-Malay Jambi Bangko dialect), (e) avoiding code-switching, (f) not interrupting conversation or suddenly changing speech, (g) giving verbal or nonverbal responses (kinesics), (h) the maxim of quantity (i) considering social distance and social status of the interlocutor; and (j) using jokes. In this research, the researcher found (1) characteristics of politeness in Indonesian in the Malay-Jambi context, (2) limits of politeness in Indonesian in the Malay-Jambi context, and (3) the scale of politeness in Indonesian in the Malay-Jambi context.